1997
DOI: 10.1116/1.580437
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of ZnO thin films on R-plane sapphire substrate by radio frequency magnetron sputtering

Abstract: ZnO thin films were deposited on a R-plane sapphire substrate. The effects of the thermal energy and the kinetic energy of the sputtered species on the growth of ZnO thin films were investigated. By varying the substrate temperature, chamber pressure, and radio frequency power, the structure of ZnO thin films was transformed from polycrystalline to epitaxial on R-plane sapphire substrates. High quality (110) ZnO epitaxial thin films were grown at the condition of 400 °C, 250 W, and 5 mTorr. According to reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…Except the unknown peak, the intensity and sharpness of the peak increase as the calcination temperature increases from 400 to 600°C, which is caused by enhanced mobility of the atoms at higher temperature. 17 The average crystallite size ͑D͒ of calcined tin oxide thin film is estimated using the Scherrer equation as follows: 18 …”
Section: B X-ray Analysismentioning
confidence: 99%
“…Except the unknown peak, the intensity and sharpness of the peak increase as the calcination temperature increases from 400 to 600°C, which is caused by enhanced mobility of the atoms at higher temperature. 17 The average crystallite size ͑D͒ of calcined tin oxide thin film is estimated using the Scherrer equation as follows: 18 …”
Section: B X-ray Analysismentioning
confidence: 99%
“…However, more highly c-axis oriented ZnO:Er films were grown at 100 W rather than at 150 W, even though higher kinetic energy could be provided to the sputtered particles at 150 W. Excessive rf powers inversely contribute to the decrease in structural order of the films due to a couple of factors, which are the high deposition rate, the relative number of Zn to ZnO ions arriving at the substrates, and the energy of secondary electrons emitted from the target. 15,16 In our work, it could be concluded that 100 W rf power was an optimal condition, while 150 W was too much for high quality films.…”
Section: Resultsmentioning
confidence: 86%
“…Further rise in growth temperature resulted in the breaking of SZO bonds and consequent resputtering of the deposited film rather than enabling the atoms to move to their stable lattice sites, producing defects in the film, and thus degrading the crystalline property. 17 Moreover, XRD measurements of SZO films, as in Fig. 1(a), did not indicate any trace of Sb or its oxide (Sb 2 O 3 ) in SZO films.…”
Section: A Structural and Morphological Propertiesmentioning
confidence: 84%